Carbon-α-Fe2O3 Composite Active Material for High-Capacity Electrodes with High Mass Loading and Flat Current Collector for Quasi-Symmetric Supercapacitors - Maedeh Najafi; Sebastiano Bellani; Valerio Galli; Marilena Isabella Zappia; Ahmad Bagheri; Milad Safarpour; Hossein Beydaghi; Matilde Eredia; Lea Pasquale; Riccardo Carzino; Simone Lauciello; Jaya-Kumar Panda; et al. (Electrochem, 2022)
In this work, we report the synthesis of an active material for supercapacitors (SCs), namely α-Fe2O3/carbon composite (C-Fe2O3) made of elongated nanoparticles linearly connected into a worm-like morphology, by means of electrospinning followed by a calcination/carbonization process. The resulting active material powder can be directly processed in the form of slurry to produce SC electrodes with mass loadings higher than 1 mg cm−2 on practical flat current collectors, avoiding the need for bulky porous substrate, as often reported in the literature. In aqueous electrolyte (6 M KOH), the so-produced C-Fe2O3 electrodes display capacity as high as ~140 mAh g−1 at a scan rate of 2 mV s−1, while showing an optimal rate capability (capacity of 32.4 mAh g−1 at a scan rate of 400 mV s−1). Thanks to their poor catalytic activity towards water splitting reactions, the electrode can operate in a wide potential range (−1.6 V–0.3 V vs. Hg/HgO), enabling the realization of performant quasi-symmetric SCs based on electrodes with the same chemical composition (but different active material mass loadings), achieving energy density approaching 10 Wh kg−1 in aqueous electrolytes.